Identification of a heteromeric interaction that influences the rectification, gating, and pH sensitivity of Kir4.1/Kir5.1 potassium channels. - Casamassima, M; D'Adamo, M; Pessia, M; Tucker, S (2003)
Heteromultimerization between different potassium channel subunits can generate channels with novel functional properties and thus contributes to the rich functional diversity of this gene family. The inwardly rectifying potassium channel subunit Kir5.1 exhibits highly selective heteromultimerization with Kir4.1 to generate heteromeric Kir4.1/Kir5.1 channels with unique rectification and kinetic properties. These novel channels are also inhibited by intracellular pH within the physiological range and are thought to play a key role in linking K+ and H+ homeostasis by the kidney. However, the mechanisms that control heteromeric K+ channel assembly and the structural elements that generate their unique functional properties are poorly understood. In this study we identify residues at an intersubunit interface between the cytoplasmic domains of Kir5.1 and Kir4.1 that influence the novel rectification and gating properties of heteromeric Kir4.1/Kir5.1 channels and that also contribute to their pH sensitivity. Furthermore, this interaction presents a structural mechanism for the functional coupling of these properties and explains how specific heteromeric interactions can contribute to the novel functional properties observed in heteromeric Kir channels. The highly conserved nature of this structural association between Kir subunits also has implications for understanding the general mechanisms of Kir channel gating and their regulation by intracellular pH.